Investigation of Pathogenic Mechanism of Covert Mortality Nodavirus Infection in Penaeus vannamei - Liu, Shuang; Xia, Jitao; Tian, Yuan; Yao, Liang; Xu, Tingting; Li, Xupeng; Li, Xiaoping; Wang, Wei; Kong, Jie; Zhang, Qingli (Frontiers in Microbiology, 2022)
Viral covert mortality disease (VCMD), also known as running mortality syndrome (RMS), is caused by covert mortality nodavirus (CMNV) and has impacted the shrimp farming industry in Asia and Latin America in recent years. The pathogenic mechanism of CMNV infecting Penaeus vannamei was investigated in this study. In the naturally infected shrimp, histopathological and in situ hybridization (ISH) analysis verified that CMNV infection and severe cellar structural damage occurred in almost all cells of the ommatidium. Under transmission electron microscopic (TEM), vacuolation and necrosis, together with numerous CMNV-like particles, could be observed in the cytoplasm of most cell types of the ommatidium. The challenge test showed that a low CMNV infectious dose caused cumulative mortality of 66.7 ± 6.7% and 33.3 ± 3.6% of shrimp in the 31-day outdoor and indoor farming trials, respectively. The shrimp in the infection group grew slower than those in the control group; the percentage of soft-shell individuals in the infection group (42.9%) was much higher than that of the control group (17.1%). The histopathological and ISH examinations of individuals artificially infected with CMNV revealed that severe cellar damage, including vacuolation, karyopyknosis, and structural failure, occurred not only in the cells of the refraction part of the ommatidium, but also in the cells of the nerve enrichment and hormone secretion zones. And the pathological damages were severe in the nerve cells of both the ventral nerve cord and segmental nerve of the pleopods. TEM examination revealed the ultrastructural pathological changes and vast amounts of CMNV-like particles in the above-mentioned tissues. The differential transcriptome analysis showed that the CMNV infection resulted in the significant down-regulated expression of genes of photo-transduction, digestion, absorption, and growth hormones, which might be the reason for the slow growth of shrimp infected by CMNV. This study uncovered unique characteristics of neurotropism of CMNV for the first time and explored the pathogenesis of slow growth and shell softening of P. vannamei caused by CMNV infection.